The Improbability of Reswitching, the Certainty of Wicksell-Effects and the Poverty of Production Functions: The Cambridge Critique of Capital Transformed - Bertram Schefold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Capital theory has taken a new turn with the theoretical discovery that wage curves tend to get linear in random systems, the larger they are. The paper by argues that reswitching becomes less likely for larger systems, while Wicksell effects are almost surely present. But it can also be shown that the elasticity of substitution is likely to be small in random systems so that a policy to lower real wages will not easily generate much additional employment in a closed economy.
Keywords: 330